Prognostic factors and survival of patients with carcinoma of the ampulla of vater after pancreaticoduodenectomy - Sunhawit Junrungsee (2018)
Background: Although carcinoma of the ampulla of Vater (CAV) is a rare tumor, accounting for just 0.2% of gastrointestinal cancers, the survival of CAV patients is unfavorable. The five-year rates have ranged from 36.8-75.2% in previous reports but there is a lack of data relating to Thai people. Also prognostic factors are controversial. Objectives: This study aimed to determine survival outcomes and to identify prognostic factors for a positive outcome for CAV patients after surgery. Methods: In this retrospective cohort study, data were collected from CAV patients who underwent surgery in Chiang Mai University Hospital from 2005 to 2012 for time to event analysis, the log rank test and univariate and multivariate Cox's regression analysis. Results: There were 72 CAV patients recruited, 45.8% being male. The mean age was 65.1 ± 10.5 years and the median waiting time for surgery was 56.5 days (24.5-91.5). The 30 day mortality rate was 5.6%., while 5-yr survival was 33.3%. The average disease free survival was 14.6 months. Prognostic factors relating to recurrence were positive lymph nodes (50% VS 19.6% p = 0.015) and advanced stage (44.1% VS 18.4% p = 0.023). Multivariate analysis showed that the potential prognostic factors for CAV patients included recurrence, moderate and poor differentiation, comorbidities and a tumor size > 2.0 cm. Conclusions: The findings of the study indicate that the overall survival of CAV patients after surgery is quite fair, with a tendency for better outcome with early as compared to advanced lesions. The key prognostic factors were recurrence, moderate and poor differentiation, comorbidity and tumor size > 2.0 cm.